The effects of participation in an educational sport programme on the motor proficiency of children with physical disabilities - Longhurst, Glynis Kay (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. in Human Movement Studies) -- Univ. of Stellenbosch, 1995.